A STYLISTIC ANALYSIS OF MODERNIST POETRY (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2024)
This article examines the stylistic features of Modernist poetry, focusing on the movement's break from traditional poetic forms, its use of fragmented structures, and its emphasis on subjectivity. Modernist poets, including T.S. Eliot, Ezra Pound, and Wallace Stevens, sought to challenge conventions by experimenting with language, imagery, and symbolism, reflecting the complexities of the early 20th-century world. This analysis highlights how these stylistic innovations reflect the core concerns of Modernism: alienation, fragmentation, and a search for meaning in a rapidly changing society.